MOTION VOCABULARY IN SUNDANESE LANGUAGE TERMINOLOGY FOR “PENCAK SILAT” A STUDY ON VOCABULARY AND WORD FORM - Siti Kamilah; Teti Sobari; Enung Nurhayati (JLER (Journal of Language Education Research), 2021)
There has been few research conducted on the vocabularies and terminology in Sundanese Language for “Pencak Silat” motion. Many variations of language terms appear in the motion of Pencak Silat. The study encopass the following material: silat motion vocabulary construction, morphemic processes contained in the vocabulary of pencak silat motion, reference meaning of silat motion and functions produced by silat motion. The research utilize the  Kridalaksana & Chaer theory to arrange the material, word class theory and  morphology. It also used Ramlan syntactic theory and semantics from Lehler theory in Pateda (2010). A qualitative method of study was used to describe the variables. Data collection was done through observation and interview. Distributional method of analysis was also utilized. The  study found terminology of Sundanese language in Pencak Silat character is unique, because the  vocabulary dose not have the same meaning as the dictionary. There is a similar vocabulary but different form and motion function, and the same motion form but different name. Research on the motion vocabulary in Pencak Silat is still very new and the research conducted is a pioneer. For future work further research from language elements or from outside the language, such as the philosophical movements of Pencak Silat is recommended.